2015
DOI: 10.1038/mt.2015.141
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Photoreceptor Outer Segment Degradation in a Human iPS Cell Model of Inherited Macular Degeneration

Abstract: Degradation of photoreceptor outer segments (POS) by retinal pigment epithelium (RPE) is essential for vision, and studies have implicated altered POS processing in the pathogenesis of some retinal degenerative diseases. Consistent with this concept, a recently established hiPSC-RPE model of inherited macular degeneration, Best disease (BD), displayed reduced rates of POS breakdown. Herein we utilized this model to determine (i) if disturbances in protein degradation pathways are associated with delayed POS di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 83 publications
1
68
0
Order By: Relevance
“…canine multifocal retinopathy, cmr ), which is caused by the same genetic defects as human bestrophinopathies, and captures the full range of clinical manifestations observed in patients (Guziewicz et al, 2007; Zangerl et al, 2010; Guziewicz et al, 2011; Beltran et al, 2014; Singh et al, 2015). To date, cBest retinopathy affects thirteen dog breeds worldwide and results from any of the three distinct mutations identified in the canine BEST1 (c BEST1 ) gene.…”
Section: Canine Models Of Human Best1-related Dystrophiesmentioning
confidence: 99%
See 1 more Smart Citation
“…canine multifocal retinopathy, cmr ), which is caused by the same genetic defects as human bestrophinopathies, and captures the full range of clinical manifestations observed in patients (Guziewicz et al, 2007; Zangerl et al, 2010; Guziewicz et al, 2011; Beltran et al, 2014; Singh et al, 2015). To date, cBest retinopathy affects thirteen dog breeds worldwide and results from any of the three distinct mutations identified in the canine BEST1 (c BEST1 ) gene.…”
Section: Canine Models Of Human Best1-related Dystrophiesmentioning
confidence: 99%
“…canine multifocal retinopathy, cmr ) (Guziewicz et al, 2007; Zangerl et al, 2010; Guziewicz et al, 2011; Beltran et al, 2014; Singh et al, 2015) to characterize lipofuscin fluorophores in the cBest1 mutant RPE, and explore factors leading to the formation of subretinal lesions in BEST1 -associated maculopathies. This study highlights matching spectral profiles of the native lipofuscin autofluorescence between human and dog bestrophinopathies, as well as robust biochemical and structural alterations at the RPE-photoreceptor interface that trigger formation of vitelliform lesions.…”
Section: Introductionmentioning
confidence: 99%
“…8 Regardless of etiology, maintaining proper RPE function is a major therapeutic target in these diseases, and currently pharmaceutical, genetic, and cellular approaches are being tested to this end in a variety of in vitro and in vivo models, as well as in clinical trials in humans. [9][10][11][12] Sodium iodate (SI, NaIO 3 ) is a chemical oxidizing agent that was reported to affect primarily the RPE causing subsequent damage to photoreceptors and additional retinal structures. 13 Whether or not primary damage occurs in additional retinal structures is still a matter of debate.…”
mentioning
confidence: 99%
“…We have previously shown that canine bestrophinopathy (cBest or cmr ) serves as an important translational model for BEST1 -associated maculopathies in man, as it recapitulates all fundamental aspects of human disease, including the salient predilection of subretinal lesions to the canine macular region (Guziewicz et al 2007; Beltran et al 2014; Singh et al 2015). In this study, cBest model proved instrumental for defining the early structural alterations at the RPE-photoreceptor interface, which may explain the susceptibility of the macula to its primary detachment in BEST1 -associated maculopathies.…”
Section: 4 Discussionmentioning
confidence: 99%
“…It is important to note that these RPE projections greatly increase the apical surface area and, consequently, the transport of signaling molecules it contains, thereby enhancing the epithelial functional capacity (Bonilha et al 2004). Thus, it is very likely that most of the major hallmarks of bestrophinopathies, e.g., disrupted ion transport, impaired phagocytosis, abnormal accumulation of autofluorescent debris in the subretinal space, and finally RPE-neuroretinal detachment and formation of serous lesions (Boon et al 2009; Singh et al 2015), arise directly from the dearth of properly formed microvilli and impaired interaction/adhesiveness with OS. The report by Bonilha et al provided strong evidence that Ezrin is a major determinant in the maturation of surface differentiations of RPE, promoting morphogenesis of apical microvilli (Bonilha et al 1999).…”
Section: 4 Discussionmentioning
confidence: 99%